The Theory of Interest in Keynes' Treatise on Money - KANO, Masao (Annals of the Society for the History of Economic Thought, 1995)
Keynes' argument that income can change without any change in the quantity of money appears in his Treatise on Money. This argument is essentially concerned with the theory of interest and the equilibrium condition in the money market, but Keynes' argument in the Treatise concerning these matters has not been sufficiently analyzed. The purpose of this paper is to clarify these matters and investigate the significance of the argument in the Treatise. In the Treatise, the total demand function for money is not specified and the money market is not theoretically related to the goods market. Then the theory of interest in the Treatise is not complete, but it can be regarded as a theory which necessarily developed into the liquidity preference theory of interest in the sense that the interest rate is governed by the excess demand for money. Furthermore, the Treatise contains valuable analysis of many subjects which are not covered in the General Theory, such as the transaction demand for money in disequilibrium and the behavior of banks.